HLA-G molecules and clinical outcome in Chronic Myeloid Leukemia. (October 2017) - Caocci, Giovanni; Greco, Marianna; Arras, Marcella; Cusano, Roberto; Orrù, Sandro; Martino, Bruno; Abruzzese, Elisabetta; Galimberti, Sara; Mulas, Olga; Trucas, Marcello; Littera, Roberto; Lai, Sara; et al.
Highlights: HLA-G molecules play a role in cancer immune-editing and NK cell inhibition. Lower event free survival in CML is associated to higher level of HLA-G. Deeper molecular response in CML is associated to lower level of HLA-G. HLA-G could represent a new useful predictive immune biomarker in CML. HLA-G is an innovative target for immune-mediated treatment approaches. Abstract: The human leukocyte antigen-G (HLA-G) gene encodes a tolerogenic protein known to promote tumor immune-escape. We investigated HLA-G polymorphisms and soluble molecules (sHLA-G) in 68 chronic myeloid leukemia (CML) patients. Patients with G*01:01:01 or G*01:01:02 allele had higher value of sHLA-G compared to G*01:01:03 (109.2 ± 39.5 vs 39.9 ± 8.8 units/ml; p = 0.03), and showed lower event free survival (EFS) (62.3% vs 90.0%; p = 0.02). The G*01:01:03 allele was associated with higher rates and earlier achievement of deep molecular response (MR) 4.5 (100% vs 65%, median of 8 vs 58 months, p = 0.001). HLA-G alleles with higher secretion of sHLA-G seem associated with lower EFS, possibly because of an inhibitory effect on the immune system. Conversely, lower levels of sHLA-G promoted achievement of MR 4.5, suggesting increased cooperation with immune system.